1992
DOI: 10.1007/bf00012835
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nematodes, fungi and bacteria on the growth of young apple trees grown in apple replant disease soil

Abstract: Growth, dry root weight of seedlings and root score of apple seedlings cv. McIntosh were reduced when soils were inoculated with Pratylenchus penetrans, Penicillium janthinellum, Constantinella terrestris, Trichoderma sp., and 4 strains of Bacillus subtilis. Trichoderma sp., and B-1 and B-26 strains of B. subtilis alone reduced plant growth but the combination of Trichoderma sp. + B. subtilis (B-l) and Trichoderma sp. + B. subtilis (B-26) increased plant height. Plant height, root weight and root score were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…This may be due to the impact of natural vegetation in fallow soils. Species of these genera have been suspected to be causal agents of replant disease (Catska et al 1988;Mazzola and Manici 2012;Utkhede et al 1992), although evidence also indicates that certain species can have a commensal or mutualistic relationship with apple plants (Vega et al 2010). Penicillium is known to be capable of the production of numerous biologically active compounds, and to act as a bacterial antagonist and plant growth promoter (Khan et al 2008;Nicoletti and de Stefano 2012).…”
Section: Fungal and Oomycete Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the impact of natural vegetation in fallow soils. Species of these genera have been suspected to be causal agents of replant disease (Catska et al 1988;Mazzola and Manici 2012;Utkhede et al 1992), although evidence also indicates that certain species can have a commensal or mutualistic relationship with apple plants (Vega et al 2010). Penicillium is known to be capable of the production of numerous biologically active compounds, and to act as a bacterial antagonist and plant growth promoter (Khan et al 2008;Nicoletti and de Stefano 2012).…”
Section: Fungal and Oomycete Analysesmentioning
confidence: 99%
“…Nonetheless, bacteria belonging to the Actinomycetes, as well as to the genera Bacillus and Pseudomonas have been implicated in ARD (Mazzola et al 2002;Mazzola and Manici 2012;Utkhede et al 1992). Certain species of Streptomyces, members of the Actinobacteria, have been reported to alleviate Rhizoctonia root infections in apple (Zhao et al 2009).…”
mentioning
confidence: 99%
“…Given the relationship of sulfur with these plants, the fact that cabbage responds well in Ontario to sulfur applications, and that a potential soil sulfur deficit could exist concurrent with various changes in sulfur use and release (Kirchmann et al 1996;McKeown and Bakker 2000), we suggest that there may be a relationship between sulfur deficiency and poor control of P. penetrans using cyanogenic plants. Furthermore, since Bacillus subtilis, a sulfur-metabolizing bacterium, has been linked with control of P. penetrans (Utkhede et al 1992), we wonder how the sulfur nutrition of bacteria affects P. penetrans directly, or in combination with acid rain potentially reducing parasites of P. penetrans. We also wonder why substantial numbers of P. penetrans females and juveniles, but no males, could be extracted from the roots of certain cultivars of the marigolds Tagetes erecta and Tagetes patula after 6 wk exposure of the plants to the nematodes (El-Zawahry et al 1998), whereas others have found Tagetes spp.…”
Section: Biodiversity and Soils Managementmentioning
confidence: 99%
“…New potential is also thought to exist in the use of rhizosphere-inhabiting bacteria, such as Pseudomonas fluorescens (Oostendorp and Sikora 1989), although Stirling (1992) considers that these will probably be commercialized in combination with other antagonists and control practices. However, as an example of the possible complications of Stirling's suggestion, Utkhede et al (1992) found increased severity of apple replant disease in the Okanagan Valley using applications of locally-isolated Bacillus subtilis along with Pratylenchus penetrans nematodes, but improved tree growth with applications of B. subtilis in combination with Trichoderma sp. fungus.…”
Section: Biodiversity and Biocontrolmentioning
confidence: 99%
“…Fungi, bacteria, and nematodes have been associated with this disease. Recently, it was shown that these agents alone as well as their interactions contribute towards the occurrence of apple replant disease in orchard soils (80).…”
Section: Soilborne Diseasesmentioning
confidence: 99%